Home based training for dexterity in Parkinson's disease: A randomized controlled trial. (August 2017) - Vanbellingen, Tim; Nyffeler, Thomas; Nigg, Julia; Janssens, Jorina; Hoppe, Johanna; Nef, Tobias; Müri, René M.; van Wegen, Erwin E.H.; Kwakkel, Gert; Bohlhalter, Stephan
Abstract: Background: Patients with Parkinson's disease exhibit disturbed manual dexterity. This impairment leads to difficulties in activities of daily living, such as buttoning a shirt or hand-writing. The aim of the present study was to investigate the effectiveness of a home-based dexterity program on fine motor skills in a single-blinded, randomized controlled trial, in patients with Parkinson's disease. Methods: One hundred and three patients with Parkinson's disease (aged between 48 and 80 years, Hoehn & Yahr stage I-IV) were randomized to either a home-based dexterity program (HOMEDEXT) or Thera-band program. All patients trained over a period of 4 weeks, 5 times/week, 30 min for each session. A baseline, post-intervention, and follow-up assessment (12 weeks later, time period without intervention) were done. The primary outcome measure was dexterity as measured with the Nine Hole peg test (9-HPT). Secondary outcome measures included strength, motor parkinsonian symptoms, dexterity-related activities of daily living (ADL) and Health-related Quality of Life (HrQoL). Results: There was a significant difference in favor of the HOMEDEXT group as compared to the Thera-band group on the primary outcome 9-HPT (p = 0.006) and dexterity-related ADL (p = 0.02) at post intervention. No significant differences were found for the other outcomes, nor at follow-up. Conclusion: This is the first randomized controlled trial showing that an intensive, task specific home-based dexterity program significantly improved fine motor skills in Parkinson's disease. The effect generalized to dexterity-related ADL functions. As these improvements did not sustain, the finding suggest that continuous training is required to maintain the benefit. Highlights: First and largest randomized home based trial for dexterity in Parkinson's disease. Task specific dexterity training (HOMEDEXT) improved dexterity in Parkinson's disease. Effect of HOMEDEXT generalized to dexterity-related ADL. Short but no long-term effects were found after a home-based dexterity training.